Resistance to mold development assessment of bio-based building materials. (1st February 2019) - Viel, Marie; Collet, Florence; Lecieux, Yann; François, Marc Louis Maurice; Colson, Valentin; Lanos, Christophe; Hussain, Atif; Lawrence, Mike
Abstract: Nowadays, insulating building materials are developed from the valorization of agro-resources. They show high ecological and hygrothermal performance. Before making them available on the market, there is a need to classify them according to their decay resistance. This paper aims to propose a test method that qualifies bio-based composites with respect to their performance. An accelerated aging test was carried out on 5 composites made with two different agro-resources (hemp and rape) and with different binders. It consists of exposing the specimens to (30 °C; 90% RH) for three months. During the test, the specimens are regularly weighed and photographed. The sample mass and the percentage of surface contaminated by fungi are measured along the test. Finally, a microscopic view allows identifying the species of the developed molds. Highlights: New rapid method for laboratory scale testing of materials resistance to molds. The fungal resistance of new bio-based buildings materials is analyzed. Mass monitoring overlaps the effect of water absorption and decay. DIC is used to analyze images. Correlation error indicates presence of mold. The pH of given building material is an important predictor of fungal susceptibility.